Acute flaccid myelitis: A clinical review of US cases 2012–2015. Issue 3 (4th August 2016) - Messacar, Kevin; Schreiner, Teri L.; Van Haren, Keith; Yang, Michele; Glaser, Carol A.; Tyler, Kenneth L.; Dominguez, Samuel R.
Abstract : This review highlights clinical features of the increasing cases of acute flaccid paralysis associated with anterior myelitis noted in the United States from 2012 to 2015. Acute flaccid myelitis refers to acute flaccid limb weakness with spinal cord gray matter lesions on imaging or evidence of spinal cord motor neuron injury on electrodiagnostic testing. Although some individuals demonstrated improvement in motor weakness and functional deficits, most have residual weakness a year or more after onset. Epidemiological evidence and biological plausibility support an association between enterovirus D68 and the recent increase in acute flaccid myelitis cases in the United States. Ann Neurol 2016;80:326–338